Role of Play in Enhancing Cognitive and Language Development of Children - Subhash, P.D.; Suresh, K.P.; Ram, Sulekha (THE PRIMARY TEACHER, 2010)
The article explores the importance of early childhood play in the natural environment to engage children in concrete and meaningful activities that enhance physical, linguistic, emotional, social, and cognitive development. Modern research in the field of ‘affective neuroscience’ has uncovered important links between playing and neurogenesis in the brain. The early childhood years could well be renamed the golden age of fantasy/pretend play in which we can see the beginning of multiple intelligences and many cognitive strategies such as joint planning, negotiation, problemsolving and goal seeking. Children exhibit an instinctual choice in their fantasy play preferences which vary according to their gender and subtle cultural divergences. Learning through fantasy play activities rooted in other cultures will also be a positive factor in helping children for an early exposure and understanding of the rich diversity of other cultures. If children lack opportunities to experience fantasy plays, it would abate their long-term capacities related to metacognition, social-cognition, and problem-solving skills. The article establishes the need to understand and frame policies and courses of action to provide such infrastructure, curriculum, teaching-learning materials and trained teachers which promote the natural-creative play preferences of the children.